Effect Of Prunus Domestica L On Omeprazole Induced Iron Deficiency Anaemia (Journal of Pharmaceutical Negative Results, 2022)
Prunus domestica L, family Rosaceae, Plums are called super-food by scientists and known for cancer prevention, digestive health, brain health, blood sugar, macular prevention and weight loss. Present study was designed for anti-anemia activity by Omeprazole induced anaemic model. Study result shows extract treated animals was Significantly increase the Hb, HCT, RBC on 15 day compared to Omeprazole alone treated animals and MCH, MCHC MCV. The result concluded that Prunus Domestica L considered as an Iron Supplement in ulcer patient or the patient taking long term treatment with proton pump inhibitor. The fruit extract had higher efficacy with higher dose 400 mg/kg and efficacy is decrease with low dose. We conclude that 200 and 400mg/kg therapeutically effective for treating iron deficiency anaemia. Based on the severity of anaemic condition adjust the dose.